E-087 Virtual Angiographic Reconstructed Projections from Four-Dimensional Digital Subtraction Angiography Acquisition, A Feasibility Study. (29th July 2016) - Pung, L; Darflinger, R; Yu, J; Alexander, M; Nicholson, A; Settecase, F; Moore, T; Amans, M; Hetts, S; Cooke, D
Abstract : Introduction/purpose: Digital subtraction angiography (DSA) remains the gold standard for the evaluation of extra- and intracranial vascular pathology. Typically, acquisition of multiple angiographic projections is needed to either elongate the vessel(s) of interest or to separate overlapping vessels. Acquiring multiple projections for each selected vessel is costly in terms of time, contrast load, and radiation exposure. Three dimensional digital subtraction angiography (3 DDSA) enabled angiographers to evaluate single vessel injections in multiple projections. Four dimensional digital subtraction angiography (4 DDSA) provides time-resolved 3D acquisition of both the arterial and venous phases of angiography. The aim of this paper is to evaluate the overall quality of processed 4 DDSA to discriminated vascular pathology from normal anatomy. Materials/methods: 3 D DSA acquisition was performed to capture primarily arterial phase (260 deg, 1.5 deg/f, rotation duration: 6 s, 172 projections, 0.36 μGy/projection) or both arterial and venous phases (260 deg, 0.85 deg/f, rotation duration: 12 s, 304 projections, 0.36 μGy/projection). Projection images obtained from the rotational acquisition were combined with the constraining 3D-DSA vascular volumes in order to form a time resolved 4 DDSA. Using an edge enhanced reconstruction kernel, the 4 DDSA volume was visualized with either a smooth or sharp image characteristic with a slice matrix of 512 × 512. This was then reconstructed into a Virtual Angiography image (Siemens). A secondary reconstruction of the mask phase of each DSA run was also performed to obtain soft tissue and bone anatomical information, from which standard biplane angiographic projections of the 4 DDSA were reconstructed. Windowing, contrast, brightness and opacity levels were adjusted. Single frame images of processed 4 DDSA acquisitions were then evaluated by our Inerventional Neuroradiology staff, as were the corresponding standard biplane projections. Images were graded on overall quality (0 = nondiagnostic, 1 = poor, 2 = acceptable, 3 = good) and ability to discriminate pathology from normal vascular anatomy. Results were compared using standard multivariate two-sample t-test. Results: Four internal carotid artery and one vertebral artery injection were evaluated. All vessels had positive findings. Evaluators identified all positive findings on both 4 DDSA and standard DSA images. There was no significant difference in ability to clear the key branch points or vessels between standard and 4 DDSA (3.84 vs. 3.65, p = 0.220). The standard DSA image quality was significantly better than 4 DDSA (20.0 vs. 11.2, p < 0.001) in composite quality scoring. Conclusions: Pathology was clearly delineated from normal vascular anatomy on 4 DDSA. However, the quality of the processed 4 DDSA images remains inferior to standard DSA projections. 4 DDSA image quality may may be improved by optimizing acquisition parameters and injection rates, but this work illustrates significant limitations in the current post-processing algorithm as the source data demonstrates better quality and resolution prior to processing. As the acquisition and post-processing software improve, single injection 4 DDSA offers distinct advantages of decreased study time, contrast dose, and radiation exposure. Disclosures: L. Pung: 5; C; Siemens Medical Solutions. R. Darflinger: None. J. Yu: None. M. Alexander: None. A. Nicholson: None. F. Settecase: None. T. Moore: 5; C; Siemens Medical Solutions. M. Amans: None. S. Hetts: None. D. Cooke: None.